Budaya Akuntansi Indonesia: Praktik Akuntansi Level Keluarga, Masyarakat, dan Bisnis - Risky Budianto; Sri Wahjuni Latifah; Novrys Suhardianto; Sri Iswati (Universitas Muhammadiyah Malang, 2023)
This study describes the accounting culture with the existence of financial cycles among Indonesian people. This research fosters the role of the philosophy of science to see accounting culture in community activities in general from its multi-paradigm perspective. There are various accounting cultures that are spread giving birth to a variety of accounting treatments that are applied in each culture. We make a qualitative systematic review as the basis for the method in this study. The results of the study show that the variety of accounting culture in Indonesia can be classified into three levels, namely the accounting culture at the family level, community level, and business level. The accounting culture that grows in Indonesia is more accountable in nature so it is not a formal object related to the recognition, measurement, and presentation of accounting information. The material object of Indonesian accounting culture is the customary practice of a society that has a social order. Systematics that are consistent and carried out continuously and passed down from generation to generation make the system a culture.